FINANCIAL PERFORMANCE ANALYSIS WITH ECONOMIC VALUE ADDED METHOD OF PT. MUSTIKA RATU TBK - Beta Deli Pratiwi; R. Deni Muhammad Danial; Dicky Joansyah (Jurnal Apresiasi Ekonomi, 2018)
PT Mustika Ratu Tbk. is a modern cosmetics and herbal medicine company listed on the Indonesia Stock Exchange. The problems that exist in PT Mustika Ratu Tbk. is on the company's Economic Value Added seen from the value of Invested Capital, NOPAT, WACC, and Capital Charges companies that fluctuate during the period 2012-2016. The purpose of this research is to know the financial performance of PT Mustika Ratu Tbk. in terms of Economic Value Added period 2012-2016. The method of analysis used in this research is descriptive method. The data used in this research is secondary data. The object of this study is the financial statements of PT. Mustika Ratu Tbk consisting of Balance Sheet and Income Statement in 2012 until 2016. The data in this research is obtained through literature study and corporate documentation. The results showed that the Economic Value Added (EVA) in 2012 amounted to 1,142,908,461 can be assessed Positive because it is above the value 0 on a predetermined benchmark, which means there has been an economic value-added process for the company. In 2013 Economic Value Added (EVA) of-944,887,103 can be rated Negative because it is below the value 0 on the benchmark that has been set, meaning there is no process of economic value-added for the company. In 2014 Economic Value Added (EVA) of -11.210.007.738 can be rated Negative because it is below the value 0 on the benchmark that has been set, meaning there is no process of economic value-added for the company. In 2015 Economic Value Added (EVA) of -10.595.194.484 can be rated Negative because it is below the value 0 on the benchmarks that have been set, meaning there is no process of economic value-added for the company. In 2016 Economic Value Added (EVA) of -17.181.300.521 can be rated Negative because it is below the value 0 on the benchmark that has been set, meaning there is no process of economic value-added for the company. Keywords: Financial Performance, Economic Value Added.[Font bold dan hanya satu alinea]